2019
DOI: 10.1103/physrevc.100.054325
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon momentum distributions in asymmetric nuclear matter

Abstract: Nucleon momentum distributions at various densities and isospin-asymmetries for nuclear matter are investigated systematically within the extended Bruecker-Hartree-Fock approach. The shapes of the normalized momentum distributions varying with k/k F are practically identical, while the density and isospin dependent magnitude of the distribution is directly related to the depletion of the Fermi sea. Based on these properties, a parameterized formula is proposed with the parameters calibrated to the calculated r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 70 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…The divergence of (50) for n b → 0 will disappear only for constant X d = 1. The relative importance of the terms proportional to k −1 nuc strongly reduces with increasing density, so that a rise driven by the σ meson contribution is observed at larger n b values, until a maximum is reached.…”
Section: Mass Shift Derivativesmentioning
confidence: 96%
See 1 more Smart Citation
“…The divergence of (50) for n b → 0 will disappear only for constant X d = 1. The relative importance of the terms proportional to k −1 nuc strongly reduces with increasing density, so that a rise driven by the σ meson contribution is observed at larger n b values, until a maximum is reached.…”
Section: Mass Shift Derivativesmentioning
confidence: 96%
“…The condensation condition allows to calculate, for a given mass-fraction function, the quasi-deuteron mass shift and its derivatives at high-densities through Eqs. (44), (47) and (50), respectively. However, the density dependence of the mass fraction X d is not known a priori, in particular at supra-saturation densities.…”
Section: Mass Shift Parameterizationmentioning
confidence: 99%
“…In the past decade the the isospin-dependent Boltzmann-Uehling-Uhlenbeck transport model (IBUU) have been very successful in describing the dynamical evolution of nucleons in phase space, as well as the reaction dynamics of heavy-ion collisions [29][30][31][32]. The present IBUU transport model originating from the IBUU04 model can describe the time evolution of the single-particle phase-space distribution function,…”
Section: The Theoretical Modelmentioning
confidence: 99%
“…Since the discovery of the atomic nucleus [1], density information has played a crucial role in the study of nuclear structure, especially in explaining the nature of nuclear force and the fundamental properties of nuclear matter [2]. For example, in studies of high-momentum tails(HMT) induced by short-range correlations(SRC), it has been found that the percentage of tails is highly dependent on the density [3][4][5]. The asymmetry potential is density-dependent, which is influenced by the Pauli blocking of the ∆-decay and the thickness of the neutron skin [6].…”
Section: Introductionmentioning
confidence: 99%